Gastric cancer in patients aged younger and older than 50 years: characteristics of gastric cancer and survival analysis - N. V. Kovalenko; V. V. Zhavoronkova; A. I. Ivanov; M. P. Postolov; S. E. Tolstopyatov; D. D. Dzhafarov; P. M. Pavlovskaya; V. A. Suvorov (Сибирский онкологический журнал)
Objective. To study clinical and pathological characteristics of gastric cancer in patients aged younger and older than 50 years, who received anticancer treatment including surgery, as well as to identify prognostic factors for overall survival of these patients.Material and methods. A retrospective study of surgical treatment outcomes was conducted in 350 gastric cancer patients, who were divided into 2 groups. The study group included 34 (9.71 %) patients aged 50 years and younger and the control group consisted of 316 (90.29 %) patients aged 51 years and older.Results. The analysis of treatment outcomes and survival rates was carried out. The diffuse-type gastric cancer was more frequently diagnosed in younger than in older patients (p<0.001), and asymptomatic disease often present in younger patients (p<0.001). There were no differences in the extent of surgery between the groups (p=0.613). The overall survival rate was lower in the control group than in the study group (p=0.002). The multivariate analysis revealed that a worse prognosis was observed in patients of the control group (hr=12.71), with regional lymph node metastases (hr=2.64), distant metastases (hr=1.83), iii/iv stage of the disease (hr=2.01), lymphovascular (hr=3.15) and perineural invasion (hr=2.46), as well as with postoperative complications (hr=2.12). Adjuvant chemotherapy improved the disease prognosis (hr=0.35).Conclusion. Specific clinical and pathological features predicted survival of gastric cancer patients aged younger and older 50 years.